Examining Users’ Assessment of Indigenous Beliefs and Practices of Alternative Medicine in Nde Division, Cameroon - Dremoh Ndeloa (European Scientific Journal, ESJ, 2024)
Despite the prevalence of conventional medical services, alternative medicine (AM) remains a vital component of healthcare-seeking choices in many communities across Africa. The persistence of indigenous beliefs and practices in healthcare decisions among the population of Nde Division, Cameroon, despite the availability of conventional Western medicine, poses a complex challenge for healthcare providers seeking to deliver effective and culturally sensitive care. This study addresses this phenomenon by exploring the role of indigenous beliefs and practices in shaping healthcare choices, using a mixed-methods approach that combines questionnaires and semistructured interviews. Questionnaire findings reveal a significant reliance on alternative medicine, with 79.59% of participants believing in the efficacy of indigenous healing traditions and 80% from the semi-structured interviews, using alternative medicine due to cultural and spiritual beliefs. Also, the strong reliance on AM is influenced by economic, social, cultural, and individual factors. Concerns around the safety and efficacy of AM highlight the need for more education, regulation, and integration with conventional healthcare, ultimately informing the development of culturally sensitive healthcare approaches.